2022
DOI: 10.1089/tmj.2021.0107
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Practice Reactivation in an Integrated Community Practice During the COVID-19 Pandemic

Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic has impacted health care organizations throughout the world. The Southwest Minnesota Region of Mayo Clinic Health System, a community-based health care system, was not immune, and in March 2020, our outpatient services were deferred and decreased by 90%. Method: This article is a review of the approach we used to safely reactivate outpatient care, the tools that we developed, and the outcomes of these reactivation efforts. A novel Outpatient Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…As a result of the pandemic, there was an increase in the demand for care and telehealth care delivery modality helped support this sudden change [3] , [4] . Previous studies comparing pre-and post-pandemic operations data found that the number of telehealth ambulatory encounters increased significantly [5] , [6] , [7] , [8] . Because telehealth allows providers to quickly adapt to the increase in demand, one study predicts that there will be a continued increase in demand for telehealth services after COVID-19 [6] .…”
Section: Introductionmentioning
confidence: 93%
“…As a result of the pandemic, there was an increase in the demand for care and telehealth care delivery modality helped support this sudden change [3] , [4] . Previous studies comparing pre-and post-pandemic operations data found that the number of telehealth ambulatory encounters increased significantly [5] , [6] , [7] , [8] . Because telehealth allows providers to quickly adapt to the increase in demand, one study predicts that there will be a continued increase in demand for telehealth services after COVID-19 [6] .…”
Section: Introductionmentioning
confidence: 93%